Steel-mixed tower system and method for improving aerodynamic performance of wind turbine - XU LU; YU WEI; KE SHITANG; DU LINGYUN; ZHU PENG; WANG HAO; YU WENLIN; WANG XIAOHAI (2017)
The invention relates to a steel-mixed tower system and method for improving aerodynamic performance of a wind turbine. A tower is formed by combining a truss and a concrete tower tube. The upper portion of the tower is of a quadrangular prism structure formed by the truss, and the lower portion of the tower is of a circular table type concrete structure. The quadrangular prism structure of the truss and steel bars in concrete are connected at the joint of the quadrangular prism structure of the truss and the lower circular table type concrete structure in a welded manner. The joint of the upper portion of the truss and a cabin is fixed through a suction cup welded to the bottom of the cabin. The perpendicular length of the quadrangular prism structure of the truss is larger than the length of blades by 5 m to 10 m. The aerodynamic performance of the steel-mixed tower system is simulated through a computational fluid dynamics method and compared with un-optimized aerodynamic force data of a tower structure, a